ANALISIS KANDUNGAN ZAT PEWARNA RHODAMIN B PADA ARUM MANIS BERDASARKAN STATUS EKONOMI PENJUAL ARUM MANIS DI SEKOLAH DASAR KECAMATAN BABAT KABUPATEN LAMONGAN - Kartikorini, Nastiti (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST)
ANALISIS KANDUNGAN ZAT PEWARNA RHODAMIN B PADA ARUM MANIS BERDASARKAN STATUS EKONOMI PENJUAL ARUM MANIS DI SEKOLAH DASAR KECAMATAN BABAT KABUPATEN LAMONGANIr. Nastiti K., M.Kes.nastitikartikorini@gmail.com Prodi D3 Analis Kesehatan UM SurabayaÂ AbstractKnowledge and economic status, including the factors that underlie the occurrence of certain behaviors. Low knowledge about food dyes potentially encourage traders using Rhodamine B as a food additive. Though dye Rhodamine B dye is additional consumer prohibited in food products. Based on the above can be taken formulation of the problem, "Are influence cotton candy vending economic status of the use of Rhodamine B dye on cotton candy sold in Elementary School District of Tripe Lamongan? purpose of the study to determine the effect of economic status cotton candy seller to use Rhodamine B dye on cotton candy Elementary School District of Tripe Lamongan. This type of research is observational analytic study population was cotton candy seller Elementary School District of Tripe Lamongan. The amount of sample is total population of 10 sellers of cotton candy in Elementary School District of Tripe Lamongan. location of sampling conducted in the Elementary School District of Tripe Lamongan. location research conducted at the Research Institute and Consulting Industry (BPKI) Surabaya - East Java. From the analysis using Chi-Square test results obtained with the significant value of 0.005 is thus P <Î± 0.05, then Ho is rejected or accepted Ha so no economic status influence on the content of cotton candy sellers Rhodamine B on cotton candy sold in the Primary School Tripe Subdistrict Lamongan. Keyword: Rhodamine B, cotton candy